Mathematics learning opportunities when playing a Tower Defense Game - Aura Hernàndez-Sabaté; Meritxell Joanpere; Núria Gorgorió; Lluís Albarracín (Serious Games Society, 2015)
A qualitative research study is presented herein with the purpose of identifying mathematics learning opportunities in a commercial version of a Tower Defense game. These learning opportunities are understood as mathematicisable moments of the game and involve the establishment of relationships between the game and mathematical problem solving. Based on the analysis of the nature of these mathematicisable moments, we present several design options that are being implemented in a didactic version of a Tower Defense game.